From Divergent Paths to the Same Trap: The Legitimacy Crisis of the Investor-State Dispute Settlement System - Sönmez, Esma Yağmur (Middle East Technical University, 2024)
This thesis critically examines a much-debated issue in international law: the legitimacy of the Investor-State Dispute Settlement system (ISDS). The system was initially conceived to provide an alternate dispute resolution mechanism for the protection and promotion of foreign investment. In time, this objective has incited a discussion on the legitimacy of the system as the developed world has started to experience the role of host states. Since then, they have taken the lead in the reform process to achieve a balance between host state's and foreign investors' rights. To this effect, both the European Union (EU) and the Third Way Approaches to International Law (TWAIL) are for centralization of the system arguing its current problems emanate from its ad hoc and decentralized nature. Although both are aimed at system centralization, the paths they take to achieve it clearly differ. The EU seeks a permanent investment court by which ad hoc arbitration would give way to a more centralized framework. However, TWAIL advocates for a return to the pre-ISDS era, where national courts resolve investment disputes between foreign investors and states. The effectiveness of these two reform ideas in addressing the purported legitimacy concerns of the ISDS is critically examined in this thesis using Martti Koskenniemi's legal approach. Ultimately, it asserts that neither proposal is adequate to resolve the legitimacy issue of the system, as legitimacy can only be achieved by strengthening the principle of justice, which is feasible alone through a more decentralized structure.
Keywords: ADR; Alternative dispute resolution; Foreign investment; Foreign investors; ISDS; Investment Dispute; Investments; Investor-State Dispute Settlement

Essays on Corporate Finance and Corporate Governance - Ding, Zijun (McMaster University, 2024)
This thesis includes three essays that examine the effects of firm policies on labor costs, corporate culture, and stock markets. The first essay studies the impact of major customers on supplier firms’ performance, and I find that supplier firms are willing to collaborate with their major customers while keeping low financial leverages. The cooperation with major customers results in higher productivity and strategic alliance, which could explain the reduction in the labor share of supplier firms. In my study, labor share is defined as the ratio of labor costs to total revenue. Compared to firms without major customers, supplier firms with at least one major customer would reduce labor shares on average by 33% in absolute terms. The findings contribute to the growing literature on the global trend of labor share reduction. The second essay examines the effect of market competition on corporate openness, which is a particular aspect of corporate culture. Corporate openness reflects how open firms are when facing new ideas and experiences, and measures firms’ willingness to innovate and cooperate. I conclude that market competition improves firms’ corporate openness through good corporate governance. Furthermore, corporate social responsibility activities are seen as a positive social outcome of corporate openness. As to economic consequences, less open firms would experience stock return reductions when the market competition is high. The third essay studies the firms listed on Chinese stock exchanges that established an internal whistleblowing mechanism. The results show that the employee whistleblowing system prevents firms from misconducting and leads to reduced stock price crash risk. Furthermore, a cooperative corporate culture helps the internal whistleblowing system decrease crash risk, while an unfair organizational climate exerts the opposite influence. Overall, this study contributes to the emerging literature on the governance role of whistleblowing.

Product Liability in a More Circular Economy : A Study of Liability for Alternative Methods of Distributing and Producing Consumer Goods - Van Gool, Elias (Université de Lille, 2024)
Specific, more strict theories of product liability, which have now largely been maximally harmonised in the EU, have developed on the basis of a linear economic model. By using doctrinal and economic legal research, this thesis examines the state of EU product liability law and how it is tested by alternative, circular economic methods of distributing and producing consumer goods, like product reuse, repurposing, resales and other retransfers, repairs, refurbishments and remanufacturing. Besides direct relevance to circular economy in the consumer goods sector, this study of so-far overlooked questions offers new theoretical insights about product liability with broader academic and practical relevance. After a general introduction to the domains of product liability and circular economy, a normative framework is developed that blends distributive justice in terms of economic efficiency with corrective justice. Subsequently, it is argued that also in a more circular economic setting a more strict product liability rule like the EU harmonisation is preferable in light of this normative framework, while the added value of product liability increases compared to its main regulatory alternatives. The thesis then studies the application to the aforementioned circular strategies of current EU product liability law based on the 1985 Directive and its almost finally adopted 2024 successor. Overall, EU product liability law turns out to be quite versatile and its relevance in a more circular consumption sector is improved by several of the new proposed rules. Nevertheless, some limitations remain and also some interpretative issues are identified in the proposed new Directive, for which amendments are proposed. Les théories spécifiques et plus strictes de la responsabilité du fait des produits, qui ont maintenant été largement harmonisées au maximum dans l'UE, se sont développées sur la base d'un modèle économique linéaire. En utilisant la recherche doctrinale et économique en droit, cette thèse examine l'état du droit européen en matière de responsabilité du fait des produits et comment il est mis à l'épreuve par des méthodes économiques alternatives et circulaires de distribution et de production de biens de consommation, comme la réutilisation des produits, le réemploi, la revente et autres retransferts, les réparations, les reconditionnements et la refabrication. Outre une pertinence directe pour l'économie circulaire dans le secteur des biens de consommation, cette étude des questions jusqu'à présent négligées offre de nouvelles perspectives théoriques sur la responsabilité du fait des produits avec une pertinence académique et pratique plus large. Après une introduction générale aux domaines de la responsabilité du fait des produits et de l'économie circulaire, un cadre normatif est développé qui mélange la justice distributive en termes d'efficacité économique avec la justice corrective. Ensuite, il est soutenu que, même dans un cadre économique plus circulaire, une règle de responsabilité du fait des produits plus stricte comme l'harmonisation de l'UE est préférable à la lumière de ce cadre normatif, tandis que la valeur ajoutée de la responsabilité du fait des produits augmente par rapport à ses principales alternatives réglementaires. La thèse étudie ensuite l'application aux stratégies circulaires susmentionnées du droit actuel de l'UE en matière de responsabilité du fait des produits basé sur la Directive de 1985 et son successeur de 2024 presque adopté. Dans l'ensemble, le droit européen en matière de responsabilité du fait des produits se révèle assez polyvalent et sa pertinence dans un secteur de consommation plus circulaire est améliorée par plusieurs des nouvelles règles proposées. Néanmoins, certaines limitations subsistent et des questions d'interprétation sont également identifiées dans la nouvelle directive proposée, pour lesquelles des amendements sont proposés.
Keywords: Accidents; Accidents de biens de consommation; Biens d'occasion; Biens de consommation; Circular economy; Commerce d'occasion; Consommateur (protection); Consumer product accidents; Product liability; Produits d'occasion; Repair; Responsabilité (droit); Responsabilité du fait des produits; Responsabilité du fait des produits (droit européen); Responsabilité du fait des services; Reuse; Réparation; Réutilisation; Second-Hand; Économie circulaire

Product Liability in a More Circular Economy : A Study of Liability for Alternative Methods of Distributing and Producing Consumer Goods - Gool, Elias van (Université de Lille ; Katholieke Universiteit Leuven, 2024)
Specific, more strict theories of product liability, which have now largely been maximally harmonised in the EU, have developed on the basis of a linear economic model. By using doctrinal and economic legal research, this thesis examines the state of EU product liability law and how it is tested by alternative, circular economic methods of distributing and producing consumer goods, like product reuse, repurposing, resales and other retransfers, repairs, refurbishments and remanufacturing. Besides direct relevance to circular economy in the consumer goods sector, this study of so-far overlooked questions offers new theoretical insights about product liability with broader academic and practical relevance. After a general introduction to the domains of product liability and circular economy, a normative framework is developed that blends distributive justice in terms of economic efficiency with corrective justice. Subsequently, it is argued that also in a more circular economic setting a more strict product liability rule like the EU harmonisation is preferable in light of this normative framework, while the added value of product liability increases compared to its main regulatory alternatives. The thesis then studies the application to the aforementioned circular strategies of current EU product liability law based on the 1985 Directive and its almost finally adopted 2024 successor. Overall, EU product liability law turns out to be quite versatile and its relevance in a more circular consumption sector is improved by several of the new proposed rules. Nevertheless, some limitations remain and also some interpretative issues are identified in the proposed new Directive, for which amendments are proposed. Les théories spécifiques et plus strictes de la responsabilité du fait des produits, qui ont maintenant été largement harmonisées au maximum dans l'UE, se sont développées sur la base d'un modèle économique linéaire. En utilisant la recherche doctrinale et économique en droit, cette thèse examine l'état du droit européen en matière de responsabilité du fait des produits et comment il est mis à l'épreuve par des méthodes économiques alternatives et circulaires de distribution et de production de biens de consommation, comme la réutilisation des produits, le réemploi, la revente et autres retransferts, les réparations, les reconditionnements et la refabrication. Outre une pertinence directe pour l'économie circulaire dans le secteur des biens de consommation, cette étude des questions jusqu'à présent négligées offre de nouvelles perspectives théoriques sur la responsabilité du fait des produits avec une pertinence académique et pratique plus large. Après une introduction générale aux domaines de la responsabilité du fait des produits et de l'économie circulaire, un cadre normatif est développé qui mélange la justice distributive en termes d'efficacité économique avec la justice corrective. Ensuite, il est soutenu que, même dans un cadre économique plus circulaire, une règle de responsabilité du fait des produits plus stricte comme l'harmonisation de l'UE est préférable à la lumière de ce cadre normatif, tandis que la valeur ajoutée de la responsabilité du fait des produits augmente par rapport à ses principales alternatives réglementaires. La thèse étudie ensuite l'application aux stratégies circulaires susmentionnées du droit actuel de l'UE en matière de responsabilité du fait des produits basé sur la Directive de 1985 et son successeur de 2024 presque adopté. Dans l'ensemble, le droit européen en matière de responsabilité du fait des produits se révèle assez polyvalent et sa pertinence dans un secteur de consommation plus circulaire est améliorée par plusieurs des nouvelles règles proposées. Néanmoins, certaines limitations subsistent et des questions d'interprétation sont également identifiées dans la nouvelle directive proposée, pour lesquelles des amendements sont proposés.
Keywords: Accidents de biens de consommation; Biens d'occasion; Circular economy; Consumer product accidents; Product liability; Repair; Responsabilité du fait des produits et du fait des services; Reuse; Réparation; Réutilisation; Second-Hand; Économie circulaire

The role and liability of internet service providers in South Africa : a critical and comparative appraisal - Nameka, Celeste Zara (University of South Africa, 2024)
This research uses a comparative approach to explore the role and liability of internet service providers in South Africa. The research aims to analyse and compare the role and liability of internet service providers for crimes and civil infractions committed by content providers and/or internet users. Against this aim, the researcher argues that internet service providers, as intermediaries, are ideally placed to monitor and control illicit content provision and/or internet use by the end user. The research focuses on South Africa, China, Ireland, and Nigeria. The research interrogated legislative control and queried the fitness for purpose of these mechanisms for internet service providers and the lacunae created by a rapidly expanding digital world comparatively. The research points out recurrent controversial and problematic concerns that affect both the internet service provider and the consumer. The researcher further explores challenges in applying legal imperatives to internet service providers that affect their end users. The comparative analysis assists in indicating how internet service providers operate in practice and their control (or lack thereof) by various legal frameworks. The researcher makes recommendations and offers solutions to assist with the future role and development of internet service providers and their impact on the end-user and criminal justice system.

Selected legal aspects of money-laundering control in trade-finance instruments - Makuyana, Tsanangurai (University of South Africa, 2024)
The traditional perception that trade-finance instruments are less susceptible to the risk of money laundering has changed due to the increasing threat of trade-based money laundering (TBML). In the process of facilitating trade-finance transactions, financial institutions may be entrapped in the dangers of TBML and be abused for criminal gains. In this regard, the institutions play a significant role in ensuring that only legitimate trade is facilitated through trade finance without being tainted by TBML. Despite that, vulnerabilities for the vice have been discovered in the trade-finance sector. This study employs a macro-comparative approach in examining how selected jurisdictions respond to the problem of TBML in trade-finance instruments. It analyses the vulnerabilities of documentary credits, documentary collections, demand guarantees and standby letters of credit to the potential risk of TBML. The thesis compares the response of the South African AML regime with that of the English, the US and Singapore AML regimes to the threat of TBML in the selected trade-finance instruments. The study reveals, inter alia, that there is not much difference between the South African AML regime and the AML regimes of the comparative jurisdictions in terms of the legislative response to the challenge of TBML in trade-finance transactions. However, the difference is apparent when it comes to the varied institutional responses to the problem within the jurisdictions considered in this thesis. While South African AML authorities have not made any official pronouncement against TBML in trade finance, those from other comparative jurisdictions have done so. The latter have also gone a step further to produce best practice reports on TBML for banks and other financial institutions involved in trade-finance transactions to enable the institutions to prepare for the challenge. However, similar to the South African position, there has not been any legislative change in the comparative jurisdictions to provide for TBML in specific terms. This means that these jurisdictions also deal with TBML using current AML legislation, which was designed originally for cash-based money-laundering operations. Therefore, the institutions and laws under the South African AML regime are relevant in the combatting of TBML. However, they may require some modifications to appropriately counter the challenge. The study makes various policy and best practice recommendations to strengthen the South African AML regime against TBML in trade-finance transactions.
Keywords: AML Regime; Bankers Association for Finance and Trade; Black Market Peso Exchange; Customer Due Diligence; Demand Guarantees; Documentary Collections; Documentary Credits; English AML Regime; FinCEN; Financial Action Task Force; Financial Intelligence Centre Act 38 of 2001; Financial Intelligence Unit; International Best Practices; International Chamber of Commerce; International Trade; Money Laundering; Money-Laundering Control; Prevention of Organised Crime Act 121 of 1998; RBA; Red-Flag Indicators; SAMLIT; Singapore AML Regime; South African AML Regime; Standby-Letters of Credits; TBML; Trade Finance; Trade-Based Money Laundering; Trade-Finance Instruments; Trade-Finance Principles; Trade-Finance Transactions; US AML Regime; World Customs Organisation; the Wolfsberg Group

Compliance with decent work standards by multinational enterprises - Maluleke, Tirhani Foster (University of Pretoria, 2024)
In contemporary times, the issue of human and labour rights violations has gained significant momentum, rendering it imperative for international organisations, states, and businesses to address this critical concern. It is widely acknowledged that while multinational enterprises can aid in achieving economic growth by investing directly overseas and raising the standard of living for the residents of host nations, their business operations may also result in abuse of human and labour rights. The United Nations (UN) Charter was drafted to set forth obligations for individual states, yet businesses do not bear international legal obligations. The Universal Declaration on Human Rights was adopted to implement the substantive contents of human rights referred to in the UN Charter in the general way. The preamble of the Universal Declaration refers to all organs of society, but, at the time of its adoption, businesses were not considered among such organs. It was inconceivable that business organisations would become so economically powerful within a few decades that they would pose a significant risk to human and labour rights, which would not be easily regulated under the national law of their host nations. It is the hypothesis of this study that numerous multinational enterprises (MNEs) violate core human and core labour rights, and that the existing regulatory framework does not adequately regulate them. To prove this hypothesis, this thesis will adopt a two phased approach. Firstly, a careful case law and literature review will reveal the inadequate regulation of MNEs. Evidence suggests that MNEs are guilty of flagrant labour standards and human rights violations. As a result of globalisation, MNEs have gained stronger international influence, and they are able to move their businesses to countries with low cost of labour and less regulations. This phenomenon weakens the governments of host nations as they are keen to promote foreign direct investment in order to reduce unemployment and to ensure economic growth. As a result, the host nations are encouraged to set laws that will attract MNEs at the expense of human and core labour rights. As result, MNEs are not held accountable in respect of their violation of human and labour rights. Secondly, this thesis will assess the efficacy of the regulatory instruments developed by the international community in response to the mentioned problem. This aspect is covered in Chapter 3 to 7 of this thesis. The strategies include the public and private hard law and soft law mechanisms developed at international level as well as campaigns by Non-Governmental Organisations (NGOs). Based on evidence, this thesis will conclude that a soft law approach is not fully effective. As such, Chapter 8 of this thesis proposes the introduction of some hard law measures to improve the existing soft law instruments to augment the existing legislative frameworks of the host countries. In particular, the thesis recommends regulatory reforms, which will empower the International Labour Organisation to intervene to prevent the labour rights violations by MNEs and where such violations occur, to at least provide effective remedies to vulnerable employees. This thesis constitutes a theoretical study, which attempts to provide suggestions regarding the implementation of realistic measures, which if implemented, may contribute to the attainment of decent work for all men and women who are engaged in work for MNEs.
Keywords: Codes of conduct; Decent work; Hard law; Human rights; Human rights due diligence; ILO MNE declaration; International Labour Organisation; International framework agreements; Labour rights; Multinational enterprises; OECD guidelines; Regional free trade agreements; Soft law

Corporate Social Responsibility Practices in the Nigerian Public Sector - Mohammed, Abbas (University of Plymouth, 2024)
This study examines Corporate Social Responsibility (CSR) practices in Nigerian public sector organisations using a comprehensive mixed-methods approach. The data collection process involved analysing 185 organisation-year observations from annual reports spanning 2011–2020, as well as questionnaires distributed to key stakeholders and interviews with senior executives from various organisations.The analysis utilised a multi-pronged strategy, including quantitative techniques such as regression analysis to explore the relationship between CSR practices and corporate governance mechanisms and qualitative methods such as narrative analysis and thematic coding to gain insights from survey responses and interviews.The findings indicate that CSR practices in the Nigerian public sector are moving in a positive direction. Organisations demonstrated commitment to CSR activities, including community development, education, environmental conservation, and philanthropy. Survey results showed that 83% of organisations engaged in CSR, driven by community acceptance and moral obligation. Additionally, 84% of organisations complied with regulatory frameworks, and 79% aligned their CSR policies with national or international standards. The analysis also found a significant positive relationship between CSR practices and factors such as larger board sizes, greater board independence, the presence of women on the board, and CEOs with longer tenures, higher educational qualifications, and international exposure.By triangulating these findings, it is clear that organisations have a strong commitment to giving back through various CSR initiatives, such as humanitarian assistance, youth empowerment, and educational programmes. Despite challenges such as budgetary constraints and weak accountability frameworks, organisations recognise the perceived benefits of CSR, including increased public confidence, improved stakeholder perceptions, enhanced organisational reputation, trust-building, community engagement, and empowering marginalised communities through education.The insights gained from this study conducted in an emerging economy namely, Nigeria, provide a new understanding of CSR practices in public-sector organisations. They also highlight the proactive approach of public sector organisations towards responsible practices. Consequently, the implications of this research extend beyond national boundaries, encouraging diverse and dedicated leadership to enhance CSR efforts and create lasting social impact. Future studies could explore comparative analysis between the public and private sectors or different countries, as well as sector-specific impact assessments.
Keywords: CSR; Corporate Social Responsibility; ESG; Sustainability

The use of blockchain for collecting value-added tax on online cross-border trade in digital goods - Kabwe, Ruddy Kapasula (University of Pretoria, 2024)
The collection of value-added tax from the cross-border supply of digital goods remains a challenge for tax authorities around the world. South Africa is no different. The traditional methods of collecting VAT from the supply of digital goods relies on the honesty of the consumer and on the supplier to account for and remit VAT to the tax authorities in the jurisdiction where the goods are consumed. The traditional collection models are often unreliable, inefficient, burdensome, and expensive for the consumers and the suppliers. The adoption of blockchain technology as a model to collect VAT on the cross-border supply of digital goods has the potential to alleviate the compliance burden on consumers and suppliers of digital goods, improve the efficiency of tax administration, and reduce VAT fraud. Importantly, blockchain technology can create trust between tax authorities, suppliers of digital goods, and consumers. This thesis critically discusses the advantages and disadvantages of implementing blockchain technology for the collection of VAT on the cross-border supply of digital goods in South Africa. This thesis unpacks the consideration factors for policymakers in the implementation of blockchain technology for the collection of VAT on cross-border trade in digital goods. The thesis makes recommendations for the South African VAT Act to be amended to make provision for the collection of VAT by utilising blockchain technology.
Keywords: Anonymisation; Blockchain technology; Decentralisation; Digital goods; Private blockchain; Smart contracts; Taxpayer privacy; Value-added tax

"Non erit innocens malus". Looking for Justice over maritime Crimes of International Concern. A tale of dichotomies - Guizzardi Righetti, Giampaolo (Université Côte d'Azur ; Università degli studi di Milano, 2024)
This dissertation is about dualities or dichotomies. In particular it investigates the interrelationships between two couple of dichotomies, the dichotomy between international and transnational crimes and the duality of land and sea as geographical and jurisdictional spaces in the attempt to answer the question of who does or should exercise its jus puniendi in case of maritime crimes of international concern. This dissertation is about dualities or dichotomies. In particular it investigates the interrelationships between two couple of dichotomies, the dichotomy between international and transnational crimes and the duality of land and sea as geographical and jurisdictional spaces in the attempt to answer the question of who does or should exercise its jus puniendi in case of maritime crimes of international concern.
Keywords: Compétence; Droit de l'homme; Droit de la mer; Justice maritime; Responsabilité (droit international); Violation des droits de l'homme; État

A comparative appraisal of creditor protection mechanisms under South African company law - Sibanda, Mandhlaenkosi (University of South Africa, 2024)
The study comparatively scrutinised creditor protection mechanisms entrenched in South African Corporate law to determine their effectiveness in advancing creditor interests in company affairs. The enquiry was triggered by the need for corporate laws to adapt to and align with the pace of global economic changes in open and democratic societies. The 2004 DTI Policy document on South African Corporate Law Reform (SACLR) proposed a shift from the traditional shareholder-centric view, which espouses shareholder importance in corporate governance, to a model that retains the supremacy of shareholder interests while simultaneously catering to the interests of other stakeholders (the enlightened shareholder value approach). In light of the DTI policy proposal, the parliament, in enacting the South African Companies Act 71 of 2008 (the Companies Act), reflected on the need to provide appropriate redress to investors' and third parties (creditors`) rights in the preamble to this piece of legislation. It was based on the forgoing expositions that this research work sought to establish whether the South African Corporate law had been adequately modelled to protect creditors and to look beyond the traditional company’s goal of profit maximisation for the shareholder at the expense of other stakeholders, such as the creditors, who equally have stakes in the success and continuation of the company. Thus, a comparative doctrinal and critical analysis of creditor protection laws from selected cognate jurisdictions was undertaken to determine the efficacy of the protection mechanisms accorded to creditors under the South African corporate jurisprudence. It is thus the researcher's findings that the South African provisions on mechanisms to protect creditors are set in motion and are, therefore, effective to a greater extent, subject to legislature dealing with some discrepancies as per lessons drawn from comparator jurisdictions and recommendations. Conclusively, the Companies Act should clearly include the creditor’s interests in those of the company and thus give a secondary duty to directors to ensure creditor interests, among other non-member stakeholders, are assertively safeguarded.
Keywords: Company controllers; Company law; Corporate entity; Corporate law; Corporate veil; Credit systems; Creditor interests; Creditor protection mechanisms; Creditors; Directors; Employees; Investors; Shareholders; Stakeholder constituencies; Stakeholder interests; Stakeholders; Third parties

A comparative legal analysis of the accommodation of neurodiversity in the workplace : towards a universal right to reasonable accommodation - Conradie, Riana (Stellenbosch University, 2024)
Workforces are made up of individuals with differences in personal characteristics, differences that may be traced back to unique personality types and traits and – sometimes – neurodivergence. Due to the inherent subjectivity of the interpersonal relationships that form the foundation of a work environment, these differences in personal characteristics inevitably lead to tension. In addition, as part of managing a work environment employers frequently take decisions that may be influenced by views and perceptions regarding employees’ personal characteristics. This study starts with a descriptive examination of the meaning of personality and the influence that personality traits and types may have on employment. This is followed by a descriptive examination of neurodivergence, the various forms of neurodivergence, and the impact of these conditions on the work environment. Building on these descriptive and conceptual underpinnings, the legal implications of neurodiversity in the workplace are investigated by identifying which principles of the existing South African employment law framework may be utilised to provide protection and promote respect for neurodiversity and the neurodiverse differences between employees. This encompasses a discussion of the South African employment law rules relating to recruitment and selection of employees, some of the rules applicable to the day-to-day management of employees, and the rules relating to termination of employment that may be (in)directly influenced by considerations of neurodiversity. The focus thereafter shifts to consider the legal principles of employment discrimination law, where it is found that the listed ground of disability and an unlisted arbitrary ground may potentially be used as the applicable grounds of discrimination by employees if they are prejudiced due to their neurodiverse characteristics. In addition, the possibility that the rules on reasonable accommodation may be utilised as primary mechanism to properly regulate neurodiversity in the work environment and protect against prejudicial treatment of employees due to their inherent personal neurodiverse characteristics is also considered. The South African position and potential employment law rules that may apply to the management of neurodiversity in the work environment is compared to the position in the United Kingdom by focusing on the meaning of disability, the right to reasonable adjustments, and the right to request flexible working arrangements. Finally, the conclusions that may be drawn from this study are emphasised and are followed by some recommendations on how (reasonable) accommodation of neurodiversity in the work environment may appropriately be used as primary mechanism to provide employees with sufficient and appropriate protection of differences in neurodiverse characteristics. Even though this study focuses on neurodiversity and neurological differences between employees, the principles and recommendations from this study may be of value in relation to the appropriate management and regulation of all inherent differences between employees.
Keywords: Discrimination in employment; Diversity in the workplace; Employment; Labor laws and legislation; Neurodivergent people; Neurodiversity; People with disabilities

Corporate law, governance, and sustainability : the public turn in the global socio-ecological transition - Junqueira, Gabriela de Oliveira (Universidade de São Paulo, 2024)
The overlap of financial, economic, ecological, and political crises has pushed the consensus on the need to promote a socio-ecological transformation, or, in short, a green transition. The discontent with the corporate world for its contributions to those crises has taken a central stage, with calls for greater corporate responsibility being articulated under a sustainability imperative. In the context of a new round of debates on the purpose of companies, this thesis examines the turning of corporate law and governance into a site for advancing a new capitalism. More specifically, the research investigates institutional changes occurring under the label of the public turn in corporate law, addressing the following questions: what constitutes the so-called public turn? What are its drivers and the perspectives on it? Which structural features led to targeting corporate law and governance to push for responsible corporate conduct? How does the public turn in corporate law relates to the broader set of actors and norms that shape corporate governance? Guided by critical approaches to the green transition and by political theories of corporate governance, the thesis resorts to different scholarships to examine the current wave of public oriented corporate governance mechanisms from within and from without corporate law. On the one side, the thesis offers a taxonomy of corporate law strategies being employed as well as a rich account on the multiple dimensions assumed by the new tools, placed at the intersection of human rights and environmental protection, corporate social responsibility, and global value chains. On the other, the thesis embeds corporate laws public turn within the unfolding of global capitalism, as the field evolves from corporate law to corporate governance to sustainable corporate governance. The thesis argues that the public turn in corporate law, caught in between the global and the local, enables the investigation of changing roles of states, businesses, and civil society within the political and epistemic terrain of the transition to a more just and sustainable economy. A sobreposição de crises financeiras, econômicas, ecológicas e políticas impulsiona o consenso sobre a necessidade de uma transformação socioecológica, ou, em resumo, uma transição verde. O descontentamento com o mundo corporativo assume centralidade, motivando demandas por mais responsabilidade corporativa, articuladas em torno de um imperativo de sustentabilidade. No contexto de uma nova rodada de debates sobre o interesse social, esta tese examina a transformação do direito societário e da governança corporativa em um locus de promoção de um 'novo capitalismo'. Mais especificamente, a pesquisa investiga as mudanças institucionais ocorrendo sob "a virada pública no direito societário", abordando as seguintes perguntas: o que constitui a esta virada? Quais são seus impulsionadores e perspectivas? Quais características estruturais levaram a mirar o direito societário e a governança para promover conduta corporativa responsável? Como a virada pública no direito societário se relaciona com o conjunto mais amplo de atores e normas que moldam a governança corporativa? Guiada por abordagens críticas da transição verde e por teorias políticas da governança corporativa, a tese recorre a diferentes correntes acadêmicas para examinar a atual onda de mecanismos de governança corporativa orientados para o público, de dentro e de fora do direito corporativo. Por um lado, a tese oferece uma taxonomia das estratégias do direito societário utilizadas, bem como um relato abrangente sobre as múltiplas dimensões assumidas pelas novas ferramentas, na interseção de direitos humanos, proteção ambiental, responsabilidade social corporativa e cadeias de valor globais. Por outro lado, a tese contextualiza a virada pública do direito societário nos desdobramentos do capitalismo global, à medida que o campo evolui do direito societário para a governança corporativa para a governança corporativa sustentável. A tese argumenta que a virada pública no direito corporativo, situada entre o global e o local, permite a investigação das mudanças nos papéis dos estados, empresas e sociedade civil no terreno político e epistêmico da transição para uma economia mais justa e sustentável.
Keywords: Corporate governance; Corporate law; Corporate sustainability; Direito societário; Economia política; Governança corporativa; Political economy; Private regulation; Regulação privada; Sustentabilidade corporativa

The legitimacy of dismissals for off-duty misconduct in South African labour law - Phulu, Thandekile (University of Pretoria, 2024)
The main aim of this thesis is to solve the uncertainties brought about by dismissals for off-duty misconduct. First, it should be acknowledged that the world as we know it has changed and continues to evolve. Dismissals have been significantly impacted by the use of social media outside the workplace. The legalisation of the use of cannabis by an adult person has also brought uncertainties in the way dismissals are handled, especially in cases where an employee consumes cannabis off-duty. These two aspects have significantly influenced dismissals for off-duty misconduct in South Africa, with employees alleging that their rights to privacy, dignity and freedom of expression are infringed. The thesis reveals that regardless of these modern changes, off-duty misconduct dismissal is still governed by the generic provisions of the Labour Relations Act 1995 and its Code of Good Practice: Dismissal. The thesis underscores the lack of clarity regarding the regulation of dismissals for off-duty misconduct in South Africa. Furthermore, despite the judiciary’s establishment of tests (the nexus test and the breakdown of the employment relationship), challenges in adjudicating off-duty misconduct cases persist. This thesis analyses the South African legal framework governing dismissals for off-duty misconduct. The research investigates the evolution of South African dismissal law, tracing its development from the pre-democratic era to the post-democratic era. This investigation scrutinises the shifts in the legal landscape regarding dismissals for off-duty misconduct. The analysis encompasses a range of legal instruments pertinent to South Africa, including legislation, international law, common law, and judicial precedent. The current need for a Code of Good Practice for off-duty misconduct dismissal is highlighted. This rationale is prompted by a comparative examination of other countries where, despite the absence of specific codes addressing off-duty misconduct, a proactive stance has been adopted to safeguard employees’ off-duty rights by enacting relevant legislation. These chosen states have statutes regulating employees’ off-duty conduct and clarifying which conduct is protected and in which circumstances. Consequently, the thesis proposes a Code of Good Practice: Dismissal for Off-duty Misconduct. This Code would assist in the uniformity of application of relevant aspects in determining the fairness of dismissals for off-duty misconduct, thus alleviating labour suits concerning this type of dismissal. The Code would also provide employers with guidelines on how to draft off-duty misconduct policies without infringing employees’ constitutional rights.
Keywords: Cannabis use; Dismissal; Labour law; Misconduct; Off-duty; Social media; South Africa

Procedural Justice in Online Dispute Resolution: An Empirical Enquiry - Beretta, Rachele (University of Antwerp, 2024)
The surge in online interactions has led to a parallel rise in civil and commercial disputes that transcend geographical boundaries. As traditional dispute resolution mechanisms face challenges adapting to this evolving paradigm, conflicts increasingly migrate to online platforms. Within this proliferating landscape, it is crucial to recognize the scarcity of research devoted to Online Dispute Resolution (ODR) providers and the myriad types of services they currently offer to users worldwide. Despite the ongoing geographical expansion of ODR, the inquiry into how procedural justice principles manifest in these digital dispute resolution systems remains notably under-explored. A growing body of literature underscores that procedural justice is critical for building users’ trust, enhancing the legitimacy of organizations among communities, and fostering compliance with outcomes. The ability of ODR providers to meet users' expectations in terms of procedural justice can significantly shape users' perception of ODR institutions as trustworthy and dependable. This bears paramount implications for the ongoing development of ODR, whose acceptance varies widely across jurisdictions. This doctoral thesis delves into the intricate intersections of procedural justice within the realm of international civil and commercial ODR, examining the nuanced dynamics that emerge in virtual spaces. Ultimately, it seeks to understand how procedural justice principles, rooted in the notion of fairness, manifest and evolve in the context of ODR, exploring the impact of digital interventions on the perceived fairness of dispute resolution processes. Understanding procedural justice in ODR is not merely an academic pursuit; it holds profound implications for legal practitioners, policymakers, and society at large. This research aims to contribute valuable insights that can inform the design of fairer and more effective ODR systems.
Keywords: Dispute Settlement; Justice; ODR; Online Dispute Resolution; Procedure (Law); UNCITRAL Arbitration Rules

Antitrust policy and EU labour markets : lessons from the US and comparative prospects - Langlois D'estaintot, Isaure (European University Institute, 2024)
Recent empirical evidence suggests that labour markets are not as competitive as previously thought. In that context, mobilizing antitrust policy has been discussed as a possible solution. The proposition sounds counterintuitive, however. If workers are paid below the competitive level, doesn’t this promote consumers’ outcomes by reducing downstream prices? Given that antitrust policy promotes consumer welfare, why would antitrust authorities intervene against such a state of affairs? Besides, why would stepping up on antitrust enforcement improve workers’ outcomes? Their interests have traditionally been protected through their exclusion from the scope of antitrust enforcement, not by the enforcement of antitrust rules to their benefit. This thesis demonstrates that those spontaneous assumptions do not hold. Consumer welfare does not speak against the defence of workers’ interests. First, the focus on consumers is a by product of methods: it does not prevent consideration of other types of market participants. Moreover, consumers benefit from competitive labour markets. The welfare effects of monopsony power simultaneously worsen workers and consumers’ outcomes. As for the promotion of workers’ interests, it can be achieved through both positive and negative enforcement of antitrust. So far, the EU Commission has been less proactive than the American DOJ and FTC on the issue of antitrust enforcement in labour markets ( although the state of affairs is evolving). While this difference may stem from EU workers benefitting from higher levels of social protection than US workers, those higher levels of protection may not negate the usefulness of antitrust ’s intervention. The low levels of antitrust enforcement in EU labour markets may result from legal uncertainty and case law inconsistency more than an absence of harm. Just like the merger control apparatus, Article 101 and 102 TFEU can be used to scrutinize labour markets. While doing so involves some practical complexities, they can be overcome.
Keywords: Antitrust law; European Union countries; Labor laws and legislation; Unfair competition

Global Common: The Rights and Responsibilities of the State and the Investor in Renewable Energy Foreign Investment - Pang, Hui (UNSW Sydney, 2024)
States poured millions of dollars to attract foreign renewable energy investments for climate change mitigation, however, when it becomes too hefty for some states, they have modified regulations to reduce the level of support. These regulation changes have led to dozens of investors filing arbitrations against the host states, alleging breaches of investment treaty obligations. This thesis examines whether the current investor-state dispute settlement (‘ISDS’) regime adequately addresses environmental concerns when adjudicating renewable energy investment cases. While renewable energy investments can help protect a global common (the atmosphere) and mitigate climate change, the regulation changes also seek to protect a domestic public good (financial stability of the host state). Therefore, when the protection of a global common conflicts with a domestic public interest in renewable energy ISDS cases, what are the rights and obligations of the host state and the investor? Are the existing approaches of the ISDS regime toward environmental concerns and other public interests fair and adequate, and if not, what interventions can be made? This thesis explores these questions by conducting doctrinal analysis on more than 60 renewable energy cases and the arbitral jurisprudence regarding international environmental obligations. It uses the constitutionalisation of international law to break the self-contained regime of international investment law and argues that common values should be regarded as equally important as investment protection goals in ISDS. This thesis finds that the ISDS regime considers international environmental obligations to be insignificant in supporting the host state’s defences in non-compliance of bilateral investment treaties or the investor’s claims for investment protection. This thesis shows that the current approach furthers discrepancies between climate change mitigation and international investment law. Not only does this approach fail to acknowledge the environmental connections of renewable energy investment, but it also creates opportunities for fossil fuel investors to seek compensation against environmental regulation changes using the same arguments. As an intervention against the current approach, this thesis proposes to reconstrue the concept of legitimate expectations to place common values on equal grounds with investment protection incentives. This thesis makes two significant contributions to knowledge. Firstly, it extends existing analyses of the conflicts and synergies between international investment law and environmental protection and contributes to the growing body of scholarship on this topic. Research on this topic has mainly focused on how the state safeguards environmental interests against investor protection claims. While this narrative comprises many cases, it does not capture the full picture and overlooks the possible contributions of private parties in protecting global commons. Instead, this thesis examines whether international environmental obligations can serve as a ‘shield’ for the state’s non-compliance in investment protection, or as a ‘sword’ for investors to compel the state to fulfil its international obligations. Secondly, this thesis makes an intervention to reconstrue ‘legitimate expectations’, where common values are reinforced and not only the interests of investors are protected but also the ‘legitimate expectations of a responsible investor’ from the state and local communities are taken into account.

Measuring the Effects of Post-Convention Activities at the HCCH - Zhang, Ke (McGill University, 2024)
Keywords: HCCH; Hague Conference on Private International Law